2022
DOI: 10.1108/itp-12-2020-0878
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a physician's prosocial behavior on the patient's choice: an empirical investigation in online health community

Abstract: PurposeThe purpose of this paper is to explore the influence of a physician’s prosocial behavior on a patient's choices in the online health community (OHC) context. Moreover, the authors explore how such effects differ across different online word-of-mouth (WOM) and professional titles.Design/methodology/approachGuided by the motivation, opportunity and ability (MOA) framework, this paper develops hypotheses and an econometric model. Then this paper used spline regression to test hypotheses on 6,204 physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Given the importance of online healthcare services, previous research has extensively investigated online information factors influencing patients' use of doctors' online healthcare services. However, extant research has mainly centered on patients' use decisions regarding online consultation services (i.e., how patients select a doctor for online consultations) (13,37,38) and offline appointment services (i.e., how patients select a doctor for offline appointments) (39)(40)(41) and has not fully investigated patients' use of doctors' OFUS, especially their effective use behaviors in this context (10).…”
Section: Online Information and Patient Decisionsmentioning
confidence: 99%
“…Given the importance of online healthcare services, previous research has extensively investigated online information factors influencing patients' use of doctors' online healthcare services. However, extant research has mainly centered on patients' use decisions regarding online consultation services (i.e., how patients select a doctor for online consultations) (13,37,38) and offline appointment services (i.e., how patients select a doctor for offline appointments) (39)(40)(41) and has not fully investigated patients' use of doctors' OFUS, especially their effective use behaviors in this context (10).…”
Section: Online Information and Patient Decisionsmentioning
confidence: 99%
“…However, spiritual and monetary incentives may affect physicians differently in relation to PHKS incentives. For instance, research has shown that monetary incentives significantly positively affect extrinsic knowledge-sharing motivation but reduce intrinsically motivated contributions by physicians (Ghose et al, 2022;Wang et al, 2022). Some researchers have explored the spillover effects of different monetary incentive levels on health experts' free knowledge contribution behavior (Qi et al, 2021).…”
Section: Monetary Incentives To Physiciansmentioning
confidence: 99%
“…For instance, research has shown that monetary incentives significantly positively affect extrinsic knowledge-sharing motivation but reduce intrinsically motivated contributions by physicians (Ghose et al. , 2022; Wang et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, a statistics report showing 4.76 billion social media users clearly depicts the mounting increase in social media usage (Chaffey, 2023). Particularly, netizens are shifting towards specific online communities 1 to engage in context‐specific activities (Chang et al, 2023; Fernandez et al, 2016; Han et al, 2018; Klassen et al, 2021; Wang, Liu, et al, 2023; Zhu et al, 2020). These specific online communities can be more effective than generic social media because they drive homophily and provide relevant and focused content, thereby ensuring utility (Andrews, 2002; Hajli, 2018; Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%